Impact of financial development on economic growth: empirical evidence from Pakistan - Jalil, Abdul; Feridun, Mete (Routledge Journals, Taylor & Francis Ltd, 2011)
The present article aims at investigating the effects of financial sector development on economic growth in the case of Pakistan from 1975 to 2008. A composite financial depth indicator is built using principal component analysis (PCA) and is used in the Autoregressive Distributed Lag (ARDL) bounds testing approach to cointegration. The results suggest the presence of a positive and significant relationship between financial development and economic growth.
Keywords: financial development; economic growth; ARDL; PCA